Rhino-orbital mucormycosis with cutaneous involvement in an HBV-positive patient: a case report and review of the literature - Sharma, Sahil; Kumar, Bhavesh; Manglik, Shivangi; Narula, Harneet Kaur; Ali, Imran; Mishra, Shreyas (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Mucormycosis is a rare fungal angioinvasive disease characterized by infarction and tissue necrosis. It is an opportunistic infection mainly affecting patients with impaired immunity, as seen in patients with diabetes mellitus with or without ketoacidosis, injudicious use of steroid therapy, hematological malignancy, bone marrow transplant, chemotherapy, neutropenia, as well with deferoxamine therapy. The various clinical variants of mucormycosis include rhino-orbitocerebral, pulmonary, cutaneous, and disseminated forms, among which the rhino-orbital-cerebral type is the most common. A notable rise in mucormycosis cases has been observed among patients with history of COVID-19. Contributing factors may consist of thromboembolic events linked to substandard oxygen administration practices, altered cardiopulmonary dynamics, and the injudicious use of steroids and antibiotics during COVID-19 treatment. Early diagnosis and urgent surgical and medical intervention form the cornerstone of a successful outcome. In our case report, we present a 55-year-old hepatitis B-positive patient with rhino-orbital mucormycosis with cutaneous involvement. This report emphasizes on the challenges faced in the management of patients with Hepatitis B-associated mucormycosis. We report a rare rhino-orbital mucormycosis (ROCM) case with cutaneous involvement in a patient with active Hepatitis B virus (HBV) infection and no other risk factors. The study emphasizes on early surgical and medical intervention and adequate control of comorbidity contributing to impaired immunity for a favorable prognosis.